Periodic Solutions of a Nonautonomous Plant-Hare Model with Impulses - Haihui Wu; Yan Zhou (Discrete Dynamics in Nature and Society)
A plant-hare model subjected by the effect of impulses is studied in this paper. Sufficient conditions are obtained for the existence of at least one positive periodic solution.